PENGARUH URBANISASI, PENDIDIKAN DAN PENDAPATAN TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) DI KOTA BANDA ACEH - M. Zawir Ghivary; Weri Weri; M. Ilhamsyah Siregar (Fakultas Ekonomi dan Bisnis UNSYIAH, 2020)
Abstract This study aims to analyze the level of urbanization, education, and income towards gross domestic product in Banda Aceh. The variables used in this study are urbanization variables, education variables and, gross domestic product variables in Banda Aceh. This study uses panel data in the period 2015-2018, and the analysis model used is a qualitative method. The results showed that the GDP and Education variables had a positive effect on immigration in Aceh. Urbanization variables showed positive results on labor growth. Labor variables show positive results on GDP growth. This study shows that all of these variables show positive results. The results of this study are expected to be one of the indicators of the government to choose policies implemented in Aceh's economy. Keywords: Urbanization, education, income, Gross Domestic Product